2002
DOI: 10.1097/00006842-200209000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Pain and Psychopathology: Research Findings and Theoretical Considerations

Abstract: Objective: Numerous studies have documented a strong association between chronic pain and psychopathology. Previous research has shown that chronic pain is most often associated with depressive disorders, anxiety disorders, somatoform disorders, substance use disorders, and personality disorders. The primary objective of this review article is to describe the nature of the relationship between chronic pain and each of these types of psychopathology. In addition, this article will explore how each of these diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
226
1
23

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 206 publications
(263 citation statements)
references
References 68 publications
9
226
1
23
Order By: Relevance
“…Moreover, affective and nociceptive pathways coincide anatomically, and the neurotransmittors serotonin and norepinephrine are involved in nociception as well as depression and anxiety [46]. It has been suggested that at least in some groups of chronic pain patients a trait of susceptibility to both pain and psychological symptoms may exist [47], perhaps due to an imbalance of the neurotransmitters involved in both conditions [46].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, affective and nociceptive pathways coincide anatomically, and the neurotransmittors serotonin and norepinephrine are involved in nociception as well as depression and anxiety [46]. It has been suggested that at least in some groups of chronic pain patients a trait of susceptibility to both pain and psychological symptoms may exist [47], perhaps due to an imbalance of the neurotransmitters involved in both conditions [46].…”
Section: Discussionmentioning
confidence: 99%
“…The various efforts to determine the causal direction between pain and depression may be organized in the following manner (Dersh et al, 2002):…”
Section: Chronic Pain and Depressionmentioning
confidence: 99%
“…For example, nociceptive (pain related) and affective pathways are thought to coincide anatomically; the neurotransmitters associated with mood disorders, namely norepinephrine and serotonin, have some involvement in the gate control mechanism described above; and antidepressant medication has been shown to relieve chronic pain (Dersh et al, 2002). It is apparent therefore that the relationship between chronic pain and depression is complex and dynamic, rather than linear and mechanistic.…”
Section: Chronic Pain and Depressionmentioning
confidence: 99%
“…Development of comorbid psychopathology also occurs at this Stage, including personality disorders, psychophysiological disorders, major depressive disorders, and substance abuse disorders (Dersh, Gatchel, Mayer, Polatin, & Temple, 2006;Dersh, Polatin, & Gatchel, 2002).…”
Section: Development Of Pain: From Acute To Chronicmentioning
confidence: 99%